Annual Report on Exchange Arrangements and Exchange Restrictions 1963. (Annual Report on Exchange Arrangements and Exchange Restrictions, 1963)
This paper outlines among the underdeveloped countries, some experienced an improvement in their balance of payments positions, enabling them to reduce restrictions on payments. Many of them, however, still had difficult balance of payments problems-because of such factors as rapid development and growth, a deterioration in their terms of trade, inflation, and other causes-and continued to apply exchange and import restrictions, or introduced additional restrictions, in an attempt to avoid undue pressure on the exchange rate and a drain on reserves. Taking a broad view of developments in the field of exchange restrictions during the past twelve months, it can be stated that it was a year of progress. The international payments system was strengthened further, and the net effect was a comparative calm in international exchange markets notwithstanding severe fluctuations on stock exchanges. The payments position and prospects of a range of countries enabled them to reduce and in some cases virtually to eliminate restrictions. Other countries that continued to experience balance of payments difficulties, such as India, Indonesia, and Ceylon, increased their import restrictions.